2020
DOI: 10.1002/aic.16987
|View full text |Cite
|
Sign up to set email alerts
|

Integration of modern computational chemistry and ASPEN PLUS for chemical process design

Abstract: Thermodynamic properties and fluid phase equilibria are crucial for the design and development of a chemical process. However, such data may not always be available, particularly for fine or specialty chemicals. In this work, we evaluate the reliability of using modern computational chemistry combined with recently developed predictive thermodynamic models to provide all the thermodynamic properties required in process design with ASPEN PLUS. Specifically, the G3 method is used for the ideal gas heat capacitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The heat of formation is among the most important thermodynamic properties of compounds. It can be used to calculate reaction enthalpies and free energies (when suitably combined with entropy values), which are paramount in a wide variety of applications in chemistry and chemical engineering such as energy storage, [1,2] chemical reaction engineering, [3][4][5] process system design, [6] combustion, [7] electrocatalysis, [8][9][10] and thermochemical and electrochemical stability assessment. [10][11][12][13][14][15][16] However, experimental heats of formation are unavailable for a vast number of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The heat of formation is among the most important thermodynamic properties of compounds. It can be used to calculate reaction enthalpies and free energies (when suitably combined with entropy values), which are paramount in a wide variety of applications in chemistry and chemical engineering such as energy storage, [1,2] chemical reaction engineering, [3][4][5] process system design, [6] combustion, [7] electrocatalysis, [8][9][10] and thermochemical and electrochemical stability assessment. [10][11][12][13][14][15][16] However, experimental heats of formation are unavailable for a vast number of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…55 Furthermore, the COSMO-SAC model has already been embedded into the latest version of Aspen Plus software because its program codes are open access (https://www.design.che.vt.edu). 56 2.2.1.1. COSMO-RS Model.…”
Section: Cosmo-based Modelsmentioning
confidence: 99%
“…Thus, in 2018 we proposed the COSMO-RS model, especially for ILs which was embedded into the Amsterdam Modeling Suite software as a separate module named after “ADF Lei 2018” to improve the predictive accuracy for the containing-ILs systems . Furthermore, the COSMO-SAC model has already been embedded into the latest version of Aspen Plus software because its program codes are open access () …”
Section: Predictive Molecular Thermodynamicsmentioning
confidence: 99%
“…The effects of solvents on CO 2 hydrogenation reaction have been widely investigated; however, the thermodynamic influence of solvent in condensed state on CO 2 hydrogenation to ethanol under various temperatures and pressures have not yet been well studied. Since calculating the properties of condensed fluid by ab initio methods require a high demand for computational resources, [23] in this work, we used Aspen Plus, which predicts the properties of condensed fluid using engineering thermodynamic models to illustrate the effects of solvents on the thermodynamics of ethanol synthesis by CO 2 hydrogenation under various temperatures and pressure. We found that the dielectric constant and the saturated vapor pressure of the solvent are of critical importance for ethanol synthesis by CO 2 hydrogenation.…”
Section: Introductionmentioning
confidence: 99%